THE EFFECT OF FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE AND REVENUE ON FINANCIAL MANAGEMENT BEHAVIOR IN THE TIME OF THE COVID-19 PANDEMIC: Case Study on Culinary Sector SMEs in Medan City - Alfida, Selia; Rina br. Bukit; Abdillah Arif (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This research was carried out on Micro, Small and Medium Enterprises (MSMEs) in the Culinary Sector of Medan City, which were registered with the Medan City Cooperatives and SMEs Service. This study aims to analyze how the Effect of Financial Knowledge, Financial Attitudes and Income on Financial Management Behavior in Micro, Small and Medium Enterprises (MSMEs) in the Culinary Sector in Medan City. This research is a quantitative research, the approach used is causality and inferential. The number of samples in this study were 90 respondents. In accordance with the formulated hypothesis, in this study the analysis of inferential statistical data was measured using the SmartPLS (Partial Least Square) software. Based on the tests that have been carried out, The direct effect significance test shows that the independent variable (Financial Knowledge, Financial Attitude, Income) has a positive and significant effect on the dependent variable (Financial Management Behavior). Financial Knowledge, Financial Attitude and Income can influence Financial Management Behavior by 63.5%.